Medical practice variations: reflections from the complex systems perspective. (1st January 2000) - Garcia, Rafael; Gonzalez-Busto, Begona; Alvarez, Yolanda
The aim of this work is to analyse medical practice variations (MPV) using a dynamic perspective. The relevance of this research lies in the fact that MPV can be considered one of the most inefficient and inequitable aspects of modern medicine. Several factors are commonly used to explain MPV such as morbidity, randomness, clinical issues or demand. On this basis, we have built a simulation model specifically excluding morbidity and demand factors and based on two main assumptions an important MPV is observed among different hospitals and health areas and a smaller MPV is observed between doctors working in the same hospital. This model is based on a main positive feedback loop, reflecting how greater experience of applying a particular course or procedure leads to a greater recommendation rate for this procedure. Therefore, the system will be highly sensitive to initial conditions, so the medical practice will become locked in a particular procedure, regardless advantages of the other procedure. Through different simulations and sensitivity analysis, we will analyse the influence that factors, such as the experience, the system's initial conditions, resource scarcity, the proportion of patients subjected to MPV and, finally, the waiting list and perverse incentives have over MPV.